Iron Speciation in Fram Strait and Over the Northeast Greenland Shelf: An Inter-Comparison Study of Voltammetric Methods - Ardiningsih, Indah; Zhu, Kechen; Lodeiro, Pablo; Gledhill, Martha; Reichart, Gert-Jan; Achterberg, Eric P.; Middag, Rob; Gerringa, Loes J. A. (Frontiers in Marine Science, 2021)
Competitive ligand exchange – adsorptive cathodic stripping voltammetry (CLE-AdCSV) is a widely used technique to determine dissolved iron (Fe) speciation in seawater, and involves competition for Fe of a known added ligand (AL) with natural organic ligands. Three different ALs were used, 2-(2-thiazolylazo)-p-cresol (TAC), salicylaldoxime (SA) and 1-nitroso-2-napthol (NN). The total ligand concentrations ([Lt]) and conditional stability constants (log K´Fe´L) obtained using the different ALs are compared. The comparison was done on seawater samples from Fram Strait and northeast Greenland shelf region, including the Norske Trough, Nioghalvfjerdsfjorden (79N) Glacier front and Westwind Trough. Data interpretation using a one-ligand model resulted in [Lt]SA (2.72 ± 0.99 nM eq Fe) > [Lt]TAC (1.77 ± 0.57 nM eq Fe) > [Lt]NN (1.57 ± 0.58 nM eq Fe); with the mean of log K´Fe´L being the highest for TAC (log K´Fe´L(TAC) = 12.8 ± 0.5), followed by SA (log K´Fe´L(SA) = 10.9 ± 0.4) and NN (log K´Fe´L(NN) = 10.1 ± 0.6). These differences are only partly explained by the detection windows employed, and are probably due to uncertainties propagated from the calibration and the heterogeneity of the natural organic ligands. An almost constant ratio of [Lt]TAC/[Lt]SA = 0.5 - 0.6 was obtained in samples over the shelf, potentially related to contributions of humic acid-type ligands. In contrast, in Fram Strait [Lt]TAC/[Lt]SA varied considerably from 0.6 to 1, indicating the influence of other ligand types, which seemed to be detected to a different extent by the TAC and SA methods. Our results show that even though the SA, TAC and NN methods have different detection windows, the results of the one ligand model captured a similar trend in [Lt], increasing from Fram Strait to the Norske Trough to the Westwind Trough. Application of a two-ligand model confirms a previous suggestion that in Polar Surface Water and in water masses over the shelf, two ligand groups existed, a relatively strong and relatively weak ligand group. The relatively weak ligand group contributed less to the total complexation capacity, hence it could only keep part of Fe released from the 79N Glacier in the dissolved phase.